2000
DOI: 10.1021/ma990654w
|View full text |Cite
|
Sign up to set email alerts
|

Surface Viscoelastic Properties of Spread Films of a Polysilylene−Poly(ethylene oxide) Multiblock Copolymer at the Air−Water Interface

Abstract: The viscoelastic properties of a spread layer of a poly(ethylene oxide)-co-poly(methylphenylsilylene) alternating block copolymer at the air-water interface have been obtained by surface quasielastic light scattering over a range of surface concentrations at a fixed capillary wavenumber and as a function of wavenumber for two surface concentrations. The frequency and the damping for a fixed capillary wavenumber showed a maximum at a surface concentration of 0.8 mg m -2 , where resonance between the capillary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Layers may be more complex than that, and other processes occurring in the adsorbed layer can potentially lead to abnormalities in the determination of the viscoelastic parameters, such as negative surface viscosities. 20,21 Work by Lopez et al 22 showed that the classic hydrodynamic model fails to determine the surface tension and the shear modulus when domains of different viscoelastic properties coexist. This leads to the measurement of apparent negative surface viscosities.…”
Section: Introductionmentioning
confidence: 99%
“…Layers may be more complex than that, and other processes occurring in the adsorbed layer can potentially lead to abnormalities in the determination of the viscoelastic parameters, such as negative surface viscosities. 20,21 Work by Lopez et al 22 showed that the classic hydrodynamic model fails to determine the surface tension and the shear modulus when domains of different viscoelastic properties coexist. This leads to the measurement of apparent negative surface viscosities.…”
Section: Introductionmentioning
confidence: 99%
“…Only spread polymer films at the liquid-gas interface have been studied relatively frequently, mainly by means of surface quasi-elastic light scattering (SQELS) (8)(9)(10)(11)(12)(13)(14)(15). This experimental technique usually leads to reasonable values of the surface pressure and the real part of the dynamic surface elasticity, which are comparable with the results of other methods, but the sign of the imaginary component of the surface elasticity proves sometimes to be in contradiction with the second law of thermodynamics (7,10,11,15). Buzza et al showed that an effective two-dimensional negative viscosity could arise if the thickness of the polymer film approaches 1 micrometer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Buzza et al showed that an effective two-dimensional negative viscosity could arise if the thickness of the polymer film approaches 1 micrometer (11). Such thickness is unreal for most systems and thus the difficulty in determining the surface viscosity probably indicates that the theory of the SQELS method is not completely adequate (4,10,15). The deviation of the transverse surface viscosity from zero in contradiction to the theory is another problem of this method (11).…”
Section: Introductionmentioning
confidence: 99%
“…The review by Olsen and Segalman gives a clear appraisal of this process and how the phase diagrams of non‐conjugated block copolymers can be modified by this behaviour 205. A wider range of aggregates become available, such as nanowires,206 corkscrews and the like 207–210…”
Section: Conjugated Rod–coil Block Copolymersmentioning
confidence: 99%